find the general solutions for each of the following
(1) Given equation is
"(3x^2+9xy+5y^2)dx-(6x^2+4xy)dy =0"
"(3x^2+9xy+5y^2)dx=(6x^2+4xy)dy"
"\\frac{dy}{dx}=\\frac{(3x^2+9xy+5y^2)}{(6x^2+4xy)}"
Putting y=vx, then "\\frac{dy}{dx}=v+x\\frac{dv}{dx}"
Then equation will be,
"v+x\\frac{dv}{dx}=\\frac{(3x^2+9vx^2+5v^2x^2)}{(6x^2+4vx^2)}"
"v+x\\frac{dv}{dx}=\\frac{(3+9v+5v^2)}{(6+4v)}"
"x\\frac{dv}{dx}=\\frac{(3+9v+5v^2)}{(6+4v)}-v"
"x\\frac{dv}{dx}=\\frac{(3+3v+v^2)}{(6+4v)}"
"\\frac{(6+4v)dv}{(3+3v+v^2)}=\\frac{dx}{x}"
Integrating both sides,
Integrating left hand side first,
"\\int \\frac{(6+4v)dv}{(3+3v+v^2)}"
Let "v^2+3v+3 = t"
"(2v+3)dv = dt"
Then integral will be,
"\\int \\frac{(6+4v)dv}{(3+3v+v^2)} = \\int \\frac{2 dt}{t} = 2ln|t| = 2ln|3+3v+v^2|"
Then, "2ln|3+3v+v^2| = ln|x| + ln|C|"
"(3+3v+v^2)^2 = Cx"
Putting v=y/x,
"(3+3(\\frac{y}{x})+(\\frac{y}{x})^2)^2 = Cx"
"(3x^2+3xy+y^2)^2 = Cx^5" is the solution of the equation.
(2) Given equation is, "x^2\\frac{dy}{dx} +xy=\\frac{y^3}{x}"
Then, "\\frac{dy}{dx} +\\frac{y}{x}=\\frac{y^3}{x^3}"
Putting y=vx, we will get,
"v+x\\frac{dy}{dx}+v = v^3"
"x\\frac{dv}{dx} = v^3-2v"
"\\frac{dv}{ v^3-2v} =\\frac{dx}{x}"
Integrating both sides,
Integrating left-hand side first, "\\int\\frac{dv}{ v^3-2v}"
"\\int\\frac{dv}{ v^3-2v} = \\int\\frac{dv}{ v(v^2-2)}"
Doing partial fraction,
"\\frac{1}{ v(v^2-2)} = \\frac{A}{v}+\\frac{Bv+C}{v^2-2}"
Solving For A, B and C, we get
"\\frac{1}{ v(v^2-2)} = \\frac{A(v^2-2)+Bv^2+Cv}{v(v^2-2)} = \\frac{(A+B)v^2+Cv-2A}{v(v^2-2)}"
Comparing powers on both sides, we get
A+B=0, C=0 and -2A=1
"\\implies A = -\\frac{1}{2} , B = \\frac{1}{2} , C=0"
Then,
"\\frac{1}{ v(v^2-2)} = \\frac{-1}{2v}+\\frac{v}{2(v^2-2)}"
Now integrating it,
"\\int\\frac{1}{ v(v^2-2)} dv=\\int \\frac{-1}{2v}+\\frac{v}{2(v^2-2)} dv"
"\\int \\frac{v}{2(v^2-2)} dv =\\int \\frac{2v}{4(v^2-2)} dv"
Taking "v^2-2 =t \\implies 2vdv = dt"
"\\int \\frac{2v}{4(v^2-2)} dv = \\int \\frac{dt}{4t} = \\frac{1}{4}ln|t|= \\frac{1}{4}ln|v^2-2|"
So, integral of LHS will be,
"\\int\\frac{1}{ v(v^2-2)} dv=\\int \\frac{-1}{2v}+\\frac{v}{2(v^2-2)} dv = -\\frac{1}{2}ln|v|+\\frac{1}{4}ln|v^2-2|"
So, we get,
"-\\frac{1}{2}ln|v|+\\frac{1}{4}ln|v^2-2| = ln|x|+ln|C|"
"-\\frac{2}{4}ln|v|+\\frac{1}{4}ln|v^2-2| = ln|x|+ln|C|"
"\\frac{1}{4}ln|\\frac{v^2-2}{v^2}| = ln|x| + ln|C|"
"\\frac{v^2-2}{v^2} = Kx^4" where K is also some constant.
putting "v = \\frac{y}{x}"
"\\frac{y^2-2x^2}{y^2} = Kx^4" which is the required solution.
Comments
Leave a comment